Analysis of the cooling effects of urban green spaces in mitigating micro-climate change using geospatial techniques in Adama City, Ethiopia - Biratu Bobo Merga; Kenate Worku Tabor; Girma Alemu Melka (Sustainable Environment, 2024)
Greening the urban environment serves as an effective strategy to counteract the impacts of localized climate variations, such as temperature fluctuations and altered precipitation patterns. The main objective of this study is to examine how urban green spaces (UGS) in Adama City contribute to cooling the surrounding areas by using geospatial methods through considering land surface temperature and vegetation cover, thereby addressing micro-climate changes. Three different remotely sensed data of Landsat7 enhanced thematic mapper plus (ETM+) of the year 2000 and 2013 as well as Landsat8 operational land imagery/thermal infrared sensor (OLI/TIRS) (2023) were used in the study. The consistent land surface temperature data were retrieved from Landsat7 ETM+ and Landsat8 OLI/TIRS using mono window and split window algorithms, respectively. Results showed that the proportion of urban green spaces to other land use/land cover was reduced from 29.3 km2 (21.20%) in 2000 to 18.17 km2 (13.15%) in 2023. Due to the increment of built-up areas and reduction of vegetation cover, the land surface temperature of the city is increasing. The analysis determined that an optimal green space area of 5.5 ± 0.5 hectares in Adama City can effectively reduce surface temperatures by approximately 2.85 degrees Celsius. This study will contribute to understanding the role of vegetation cover in reducing urban heat effect, and also assist policymakers in regard to urban land use planning.